How Should HIV Resources be Allocated? Lessons Learnt from Applying Optima HIV in 23 Countries - Stuart, Robyn M.; Grobicki, Laura; Haghparast-Bidgoli, Hassan; Panovska-Griffiths, Jasmina; Skordis, Jolene; Keiser, Olivia; Estill, Janne; Baranczuk, Zofia; Kelly, Sherrie L.; Reporter, Iyanoosh; Kedziora, David J.; Shattock, Andrew J.; et al. (Wiley, 2019)
With limited funds available, meeting global health targets requires countries to both mobilize and prioritize their health spending. Within this context, countries have recognized the importance of allocating funds for HIV as efficiently as possible to maximize impact. Over the past six years, the governments of 23 countries in Africa, Asia, Eastern Europe and Latin America have used the Optima HIV tool to estimate the optimal allocation of HIV resources.